Research on Seismic Security Evaluation Model and Route Reconfiguration Algorithm for Public Communication Networks - Han, Mingchao; Sun, Guoliang; Li, Xiangping; Zhang, Xuezhong; Ji, Shuqiang (Proceedings (International Conference on Communication Technology. Online), 2024)
Seismic disaster would cause overall performance degradation or even failure of public communication networks. To analyze the security performance of networks responding to seismic disasters scenarios, a nodes-lines evaluation model is proposed based on graph theory and Monte Carlo method, which clarifies the mathematical probability relationship between seismic parameter and performance of the networks. And then, we present a post-disaster route reconfiguration algorithm with optimal recovery time as objective function considering social dimensions. Finally, two cases analysis are given which verify the feasibility of the proposed evaluation model and route algorithm respectively. This research provides effective methodologies for seismic security evaluation and rapid post-disaster recovery of public communication networks.